2020
DOI: 10.1186/s12888-020-02723-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of assertive case management intervention on suicide attempters with comorbid Axis I and II psychiatric diagnoses: secondary analysis of a randomised controlled trial

Abstract: Background: Most suicide attempters suffer from psychiatric disorders, which are often comorbid with personality disorders. The effects of intervention on patients who have attempted suicide with comorbid Axis I and II diagnoses have not been fully elucidated. We evaluated whether assertive case management can reduce the repetition of suicidal behaviours in patients who had attempted suicide with comorbid Axis I and II diagnoses. Methods: This study was a secondary analysis of a randomised controlled trial inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…Prior studies in hospitals and community-based settings focusing on implementing strategies for suicide prevention have shown promising results with reduction in suicide attempts in the intervention group [7][8][9]. Our results corroborate with prior findings and further strengthen the consensus that individuals with high risk for suicide need proper care coordination with strong support from families and mental health professionals to address their needs and overall well-being.…”
Section: Discussionsupporting
confidence: 88%
“…Prior studies in hospitals and community-based settings focusing on implementing strategies for suicide prevention have shown promising results with reduction in suicide attempts in the intervention group [7][8][9]. Our results corroborate with prior findings and further strengthen the consensus that individuals with high risk for suicide need proper care coordination with strong support from families and mental health professionals to address their needs and overall well-being.…”
Section: Discussionsupporting
confidence: 88%
“…Furuno et al (2018) found that assertive case management reduced the number of overall self‐harm episodes (adjusted incidence risk ratio [IRR] 0.88, 95%; CI, 0.80‐0.96; P = .0031). Norimoto et al (2020) also showed that this case management was effective in patients with comorbid DSM‐IV Axis I, that is, all psychological diagnostic categories except intellectual disability and personality disorder, and Axis II diagnoses, that is, personality disorders and intellectual disability, as well as only Axis I diagnoses (risk ratio of Axis I + Axis II: 0.44, 95%; CI 0.14‐1.40). In summary, the ACTION‐J study provided strong evidence for the effective prevention of recurrent suicide attempts.…”
Section: Strategic Studies For Suicide Prevention (2006‐2011): Japanese Multimodal Intervention Trials For Suicide Prevention (J‐misp)mentioning
confidence: 98%
“…The ACTION‐J Study showed that a 6‐month assertive case management intervention effectively prevented suicide reattempts over 6 months by those with a history of attempts 7–9 . Subsequent secondary analyses of ACTION‐J data also revealed that assertive case management helped prevent suicide reattempts among patients with comorbid DSM‐IV‐TR Axis I and II disorders 11 and those with a history of self‐poisoning, 12 and reduced the overall incidence of self‐harm 13 . The secondary analysis also elucidated the importance of visits to a psychiatrist a short time before the first suicide attempt in men and in women with substance‐related disorder, previous suicide attempts, and drug overdose in the first suicide attempt as predictive factors for future suicide reattempts 14 …”
Section: Discussionmentioning
confidence: 99%